Association of proton pump inhibitor use and significant hyponatremia—a US population-based case-control study. Issue 4 (9th June 2022) - El-Alali, Emran; Al Jaber, Emad
Abstract: Hyponatremia is the most common electrolyte abnormality encountered in clinical practice. Several medications are associated with hyponatremia. Proton pump inhibitors were reported to cause hyponatremia in one large Swedish population-based study and small observational studies or case reports. This article presents the results of a single-center retrospective case-control study based on a US patient population that examined the association between the use of proton pump inhibitors and significant hyponatremia. Cases were 792 hospitalized patients with hyponatremia, extracted from 473, 000 patient encounters over 6 years, and matched controls were 774 hospitalized patients with normal serum sodium levels whose risk factors for hyponatremia were comparable to those of the study cases. The results showed that use of proton pump inhibitors for at least 30 days prior to hospital admission was significantly higher in patients with hyponatremia than in patients who had normal serum sodium levels (32.7% vs 23.3%, respectively, odds ratio 1.6, P < 0.001). Also, proton pump inhibitor use was nonsignificantly higher among patients with recurrent hyponatremia in subsequent hospitalizations compared with patients who did not have recurrence of hyponatremia (35.5% vs 30.4%, respectively, odds ratio 1.3, P = 0.13). To our knowledge, no prior US population-based study addressing such an association has been published.